2018
DOI: 10.1111/jfpe.12944
|View full text |Cite
|
Sign up to set email alerts
|

UV‐C treatment on the safety of skim milk: Effect on microbial inactivation and cytotoxicity evaluation

Abstract: The efficacy of UV‐C irradiation as a nonthermal processing method for skim milk (SM) was investigated. SM inoculated with two surrogate viruses (MS2 and T1UV), and three bacteria (Escherichia coli ATCC 25922, Salmonella enterica serovar Typhimurium ATCC 13311, and Listeria monocytogenes ATCC 19115) was treated with Deanflow UV‐C irradiation, a spiral reactor with the fluid pumped around a central low‐pressure mercury UV lamp (40 W) emitting at 254 nm wave‐length. A series of known UV doses (0–168.33 mJ·cm2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
2
17
0
1
Order By: Relevance
“…However, we are yet to evaluate the characteristics of the degradation compounds from the UV-treated samples from our experimental conditions. Our results are in accordance with some of other UV-related studies with no toxic effect on the irradiated i.e., coconut water (Bhullar et al, 2018), skim milk (Ward et al, 2019), and apple juice (Chandra et al, 2017). The HepG2 cytotoxicity study on UV irradiated ultrapure water also demonstrated no significant loss of the active cells (Stanley et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, we are yet to evaluate the characteristics of the degradation compounds from the UV-treated samples from our experimental conditions. Our results are in accordance with some of other UV-related studies with no toxic effect on the irradiated i.e., coconut water (Bhullar et al, 2018), skim milk (Ward et al, 2019), and apple juice (Chandra et al, 2017). The HepG2 cytotoxicity study on UV irradiated ultrapure water also demonstrated no significant loss of the active cells (Stanley et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The device was initially calibrated to 100 percent and 0 percent baseline. Optical properties were measured as per the method described by (Ward et al, 2019). Ultraviolet transmittance (UV- A T %/cm), which is a calculation of the fraction of incident light transmitted along the 1 cm path-length of the sample, was measured using eq.…”
Section: Methodsmentioning
confidence: 99%
“…The inactivation of viruses in liquid foods has been studied using coconut water [ 150 , 151 ] and skim milk [ 152 , 153 ] challenged with phages MS2 and T1UV in two types of experimental set-up: collimated beam in a stirred batch reactor and a Dean vortex continuous reactor. Reductions in viral titer reached 4 log cycles for MS2 and more than 5 log for T1UV in coconut water [ 150 , 151 ] and at least 5 log for both MS2 and T1UV in skim milk [ 152 , 153 ]. It is widely known that the efficacy of UV treatments of liquid foods decreases with turbidity and suspended solids, which absorb or scatter the light before reaching the viral particles.…”
Section: Impact Of Uv Treatment On Foods and Food-related Matrices (Liquids And Surfaces)mentioning
confidence: 99%
“…The formation of potentially toxic compounds due to the action of UV light on food components was also examined. No cytotoxicity was observed when skim milk was treated with up to 0.17 J/cm 2 [ 153 ] or coconut water with up to 0.4 J/cm 2 [ 151 ], fluences that were high enough to reduce viral titers substantially.…”
Section: Impact Of Uv Treatment On Foods and Food-related Matrices (Liquids And Surfaces)mentioning
confidence: 99%
“…A variety of approaches have therefore been developed to decontaminate food, water, air, and surfaces that may contain infective viruses (2)(3)(4)(5)(6)(7). UV254 treatment, in particular, is gaining popularity as an alternative to more traditional chemical disinfection strategies (8)(9)(10). Viruses can have highly variable UV254 susceptibilities (11,12).…”
Section: Introductionmentioning
confidence: 99%